2001
DOI: 10.1161/01.cir.103.24.2980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Balloon Injury on Neointimal Hyperplasia in Streptozotocin-Induced Diabetes and in Hyperinsulinemic Nondiabetic Pancreatic Islet–Transplanted Rats

Abstract: In rats with streptozotocin-induced diabetes, balloon injury was not associated with an increase in neointimal formation. Exogenous insulin administration in diabetic rats and islet transplantation in nondiabetic rats increased both blood insulin levels and neointimal hyperplasia after balloon injury. Hyperinsulinemia through activation of the ras/MAPK pathway, rather than hyperglycemia per se, seems to be of crucial importance in determining the exaggerated neointimal hyperplasia after balloon angioplasty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 38 publications
7
97
1
1
Order By: Relevance
“…24,25 Balloon injury activates the MAPK pathway in diabetics, and hyperinsulinemia activation of the MAPK pathway has been shown to be of importance in the exaggerated neointimal hyperplasia after balloon injury in diabetic animals. 26 Blockade of RAGE/ ligand interaction decreases MAPK activity in cultured SMCs in a concentration-dependent manner. 27 Inhibition of RAGE/ ligand interaction decreased tumor cell proliferation and invasion by suppressing the activation of p44/p42, p38, and SAP/JNK MAP Kinases pathways.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Balloon injury activates the MAPK pathway in diabetics, and hyperinsulinemia activation of the MAPK pathway has been shown to be of importance in the exaggerated neointimal hyperplasia after balloon injury in diabetic animals. 26 Blockade of RAGE/ ligand interaction decreases MAPK activity in cultured SMCs in a concentration-dependent manner. 27 Inhibition of RAGE/ ligand interaction decreased tumor cell proliferation and invasion by suppressing the activation of p44/p42, p38, and SAP/JNK MAP Kinases pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on recent studies indicating that neointimal enlargement may be dependent on elevated insulin rather than elevated glucose levels. 2,3 Interestingly, one of these studies 3 found that hyperinsulinemia without diabetes also resulted in enhanced neointima formation after vascular injury, a finding that underscores the pivotal role of elevated insulin as a vascular pathogen. Other studies have reported that diabetes may be associated with NO deficiency, 16 a finding that could explain the tendency of insulin to enhance neointimal formation in vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin stimulated the motility of aortic smooth muscle cells by Ϸ3-fold, confirming a recent report. 3 Conversely, the NO donor SNAP attenuated the capacity of insulin to stimulate cell motility by Ͼ80% (please see online Figure I, which can be accessed at http://atvb.ahajournals.org).…”
Section: No Blocks Insulin-stimulated Cell Motilitymentioning
confidence: 99%
See 2 more Smart Citations